Relevansi Konsep Uang Perspektif Ibnu Miskawaih di Era Modernisasi - Desi Handayani; Syifa Nurulia; Udin Saripudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The concept of money has evolved over time with the development of civilization and human needs. Money can be defined by its functions, namely as a medium of exchange and as a standard of payment. Ibn Miskawaih had insightful thoughts on the concept of money. This research aims to examine Ibn Miskawaih's concept of money and the relevance of his thoughts to the current era of modernization. The research utilizes a literature review design with a historical and descriptive approach. The selected data collection technique is documentation, which involves reviewing literature relevant to the chosen title. The results of this research show that Ibn Miskawaih has a comprehensive approach to the concept of money. According to him, money serves as a medium of exchange, a standard of value, and to prevent injustice in economic transactions. He also asserts that among various forms of money, only gold and silver qualify as true money. Ibn Miskawaih also discusses the role of money in the Islamic economy, as well as the importance of money in measuring the price of each commodity and service.